A Chinese Child Presented with Early T Cell Precursor Lymphoblastic Lymphoma - Pu, Xiangyang; Deng, Shengyong; Yin, Nange; Song, Lin; He, Xiangling; Xiao, Jianwen (Case Reports in Hematology, 2021)
T cell lymphoblastic lymphoma (T-LBL) is regarded as the leukemic phase of T cell acute lymphoblastic leukemia (T-ALL). The early T cell precursors ALL/LBL (ETP-LBL/ALL) are derived from thymic cells at the ETP differentiation stage and recognized as a high-risk subgroup of T-ALL/LBL. Most of these cases presented with ALL at the disease onset, but the ETP-LBL phase is uncommon. Here, we report a patient who presented with ETP-LBL at the disease onset. In this case, ALL developed even despite receiving chemotherapy, but the patient achieved a complete remission with intensive chemotherapy.